Influência da complexidade do substrato na ecologia das comunidades de Chironomidae (Diptera) - Mazão, Gustavo Rincon (2013)
With the purpose of elucidating some aspects concerning the importance of substrate spatial complexity to the ecology of Chironomidae (Diptera) family in Cerrado streams, three field experiments were carried out in Ipameri and Mimoso de Goiás Municipalities, Goiás State, Brazil. These experiments are described in three chapters that compose this thesis i) Temporal dynamics of Chironomidae (Diptera) larvae on substrates with different levels of spatial complexity and roughness in a Central Brazil stream; ii) Is substrate complexity important for Chironomidae (Diptera) larvae to resist hydrological disturbance?; iii) Influence of spatial complexity and roughness on Chironomidae (Diptera) assemblages. Artificial substrates with different complexity and roughness levels were fixed in bed streams for colonization of Chironomidae larvae. Samplings were taken after a period of 30 days. Results indicated that: i) Colonization of substrates by larvae was not influenced by substrate spatial complexity and no patterns of colonization were observed, considering the various ecological guilds; ii) Both complexity and roughness were not sufficient to maintain the abundance of these organisms, evidencing their sensibility to sudden rain events; iii) Spatial complexity and roughness of substrate influenced the structure of Chironomidade assemblages and were two important aspects to the diversity of these organisms.